WACANA PERKAWINAN DALAM NOVEL SENTANA CUCU MAREP KARYA I MADE SUGIANTO : ANALISIS SOSIOLOGI SASTRA - Rama Ariesta Jaya, Kadek (Humanis; Volume 15. No.2. Mei 2016, 2016)
This study entitled "Wacana Perkawinan dalam Novel Sentana Cucu Marep Karya I Made Sugianto: Analisis Sosiologi Sastra". This study uses Structural theory and the theory Sociology of Literature. This study aims to describe the structure of the build Novel Sentana Cucu Marep and examine and analyze various forms of marriage are reflected in the Novel Sentana Cucu Marep. The stage of providing data using methods refer to the technical note. In addition, using interviews with recording techniques and techniques recorded note that important things were obtained from interviews. Furthermore, in the stage of data analysis using descriptive qualitative method. In this stage also supported by descriptive analytical techniques. At the stage of presentation of data analysis, the method used is the informal method. The structure of the build Novel Sentana Cucu Marep there are six that incident, plot, setting, character and characterization, theme, and the mandate, (2) forms of marriage contained in the Novel Sentana Cucu Marep namely marriage nyeburin/nyentana, majangkepan marriage, marriage different dynasty (asupundung), and marriage on pada gelahang. While the method or system of customary law marriage by Bali today is known that there are two ways, namely by way of marriage mamadik and marriage by means ngerorod (run together). Both methods are chosen depending on the engagement process (magelanan). (3) the author's view regarding the prohibition of marriage is marriage with the next of kin (gamia gamana) and meras pianak solution to continue Swadharma (liabilities).
Keywords: Novel, Structure, Marriage.